Description of Internet-based Information on Sexual and Reproductive Health and rights (SRHR) in High Schools - Afriyatin, Via; Handayani, Oktia Woro Kasmini; Indarjo, Sofwan (Universitas Negeri Semarang, 2025)
The internet has become an essential source of information for adolescents, especially when it comes to accessing information about reproductive and sexual health. However, inadequate access to accurate reproductive and sexual health information, minimal parental supervision, and a culture that considers sexuality a taboo topic make adolescents vulnerable to misinformation and risky behavior. The absence of sex education in schools and limited access to reproductive health services further exacerbate this problem. On the other hand, the SDG 2030 target emphasizes universal access to reproductive health information and services. This study focuses on how high school students understand and evaluate reproductive and sexual health information from the internet and the factors that influence their access and interpretation. This study uses a qualitative approach with a case study design. Informants were selected using purposive sampling and snowball sampling techniques. The research subjects were students from SMK X and SMA Y Semarang. In this study, saturation was achieved in the 10th interview with the primary informants (students aged 15-19 years) with an interview duration of 30-45 minutes per informant. In addition, there were four triangulations of teachers and two triangulations of close friends. Data analysis was performed using thematic analysis with NVivo 12 software. The results show that the internet is the primary source of reproductive and sexual health information for adolescents, but their ability to sort information is still limited. Cultural barriers, conservative norms, and generational gaps hinder open communication, while family and school support remain weak. There is a need to integrate SRH material into the curriculum, train teachers, and improve adolescents' digital literacy through collaboration between families, schools, and communities.